Cultural Danger of Globalisation for the Islamic World - Bakr, Rafique Abu (IIUC Studies, 2009)
The full text of this article is in Arabic - see PDF below. doi: 10.3329/iiucs.v4i0.2858 IIUC STUDIES Vol. - 4, December 2007 (p 49-58)